Lymph node yield in right colectomy for cancer: a comparison of open, laparoscopic and robotic approaches. (3rd October 2017) - Widmar, M.; Keskin, M.; Strombom, P.; Beltran, P.; Chow, O. S.; Smith, J. J.; Nash, G. M.; Shia, J.; Russell, D.; Garcia‐Aguilar, J.
Abstract: Aim: Studies have demonstrated a relationship between lymph node (LN) yield and survival after colectomy for cancer. The impact of surgical technique on LN yield has not been well explored. Method: This is a retrospective study of right colectomy (RC) for cancer at a single institution from 2012 to 2014. Exclusion criteria were previous colectomy and emergent and palliative operations. All data were collected by chart review. Primary outcomes were LN yield and the LN to length of surgical specimen (LN‐LSS) ratio. Multivariable mixed models were created with surgeon and pathologist as random effects. Sensitivity analyses were performed to exclude Stage IV cancers and to analyse groups on an 'as‐treated' basis. Results: We identified 181 open (O‐RC), 163 laparoscopic (L‐RC) and 119 robotic (R‐RC) right colectomies. O‐RC was more commonly performed in women with metastatic disease. The mean LN yield was 28, 29 and 34 in O‐RC, L‐RC and R‐RC, respectively; the respective mean LN‐LSS ratios were 0.83, 0.91 and 1.0. The R‐RC approach produced a higher LN yield than the other approaches ( P  <   0.01), and a higher LN‐LSS ratio than O‐RC ( P  <   0.01). These findings were unchanged in sensitivity analyses. Conclusion: Robotic right colectomy improves LN yield and the LN‐LSS ratio, which may reflect better mesocolic excision. The effect of these findings on survival requires further investigation.